Gereja Persekutuan Umat Allah - Novry Dien (Media (Jurnal Filsafat dan Teologi), 2020)
This essay deals with the idea of the church as the people of God according to Lumen Gentium, a Second Vatican Council’s document on the Catholic Church. The author tries to explore and understand the historical background of this idea and its development. This idea can be traced in the patristic time when the church was still limited to some small communities in which the leadership of the church was more charismatic. As the Church grew bigger and needed to be organized, the role of the hierarchy was clearly emphasized and enjoyed its almost absolute privilege during the Middle Ages. The Church restored its initial understanding in the Second Vatican Council which opened the windows for active role of the lay persons in the life of the church, working together with the hierarchy to present salvation to the world. This essay also tries to explore some problem regarding this idea which arose in ecclesiological discourse after the Second Vatican Council.